Differential effects of focused and unfocused recasts on EFL learners’ oral accuracy - Ansarin, Ali Akbar; Chehrazad, Mohammad Hassan (Colombian Applied Linguistics Journal, 2015)
One of the limitations of meaning-focused instruction in the EFL context is that a communicative approach is not sufficient enough to ensure higher levels of oral accuracy. The purpose of the current study was to investigate the effects of two different focus-on-form techniques, unfocused and focused recasts, on EFL learners’ oral accuracy. Three pre-intermediate intact classes were randomly selected as the focused recast, unfocused recast, and control groups. In the focused recast group, the focus of correction was on simple past tense errors. In the unfocused recast group, the recast was provided for all errors. In the control group, there was no corrective feedback. Learners’ oral accuracy as the number of Error-free T-units per T-units was measured. One-way ANOVAs indicated that the differences among groups were only significant in sessions five and six. Tukey’s HSD (honest significant difference) indicated that the focused recast group outperformed both the unfocused and the control groups in these sessions and there were no significant differences between the other two groups. These findings suggest that focus on form can be an effective tool for the development of the oral accuracy in EFL situations. In addition, recasting learners’ oral errors could enhance oral accuracy.